Analysis of ballistic waves in seismic noise monitoring of water table variations in a water field site: added value from numerical modelling to data understanding. Issue 3 (2nd September 2019) - Garambois, S; Voisin, C; Romero Guzman, M A; Brito, D; Guillier, B; Réfloch, A
SUMMARY: Passive seismic interferometry allows to track continuously the weak seismic velocity changes in any medium by correlating the ambient seismic noise between two points to reconstruct the Green's function. The ballistic surface waves of the reconstructed Green's functions are used to monitor the changes of water table induced by a controlled experiment in the Crépieux-Charmy (France) exploitation field. Viscoelastic numerical modelling of the monitoring experiment reproduces quite satisfactorily the sensitivity of the surface waves to the water table previously observed with seismic noise data. This numerical approach points out that this sensitivity is controlled by mode mixing of Rayleigh waves. It also made it possible to identify the refracted P wave and to extract its anticorrelated sensitivity to water table variations. Depending on the offset between receivers, it was observed numerically that the interferences between the different waves (with different velocities) composing the seismic wavefield slightly affect the quantitative sensitivity to water table changes. This suggests the use of an optimal spatial and temporal observation window for which wave interference is minor and does not blur the quantitative response to water table variations. We were thus able to determine the relationship between velocity and water table variations for all waves involved. From numerical computations, we identify a weak signal-to-noise ratio phase in the noise correlograms, with a anticorrelated sensitivity to the water table: the reconstructed refracted waves.